The translation of mythical intertextuality in Darwish’s Mural “Jidariat Darwish” - Alderbashi, Bilal; Alshbeekat, Aseel (Penerbit Universiti Kebangsaan Malaysia, 2023)
The Palestinian poet, Mahmoud Darwish, is a master of weaving various intellectual sources and different types of religious, artistic, historical, and mythical figures into his poetry. Like any exceptional piece of art, his poetry triggers an immediate response. It blends the aesthetic with the informative to create a vivid world deeply rooted in global heritage and local folklore. This paper investigates the translation strategies of mythical intertextuality in Darwish's poem "Mural.” The current paper is a product-oriented descriptive translation study that uses a contrastive analysis of three published translations to analyse the translation strategies. The mythical intertextuality is located in the source text then each example is mapped to its counterparts in the target texts. This study aims to identify the strategies used in translating the Arabic mythical intertextuality into English, find the impediments hindering the translation process, and reach a generalisation about the translators' norms and patterns of translation. The study concludes that regardless of the strategy applied to translate mythical intertextuality, what truly affects the process and product of translation is the translator's cultural accumulative knowledge, i.e. the translator's cultural infrastructure. This knowledge, which enables the translator to perform his vital role as an informed reader, facilitates the task of rendering the mythical intertextuality, which can be studied as a representative of all types of intertextuality, with all its cultural aspects, connections and background.